HUBUNGAN DAYA TARIK DAN EDUKASI BUDAYA DIGITAL TERBADAP MINAT WISATAWAN MENGUNJUNGI RUANG IMERSIFA MUSEUM NASIONAL INDONESIA - Nilam Dwi Cahyaningrum; Ramang H Demolingo (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2026)
ABSTRACTLow museum attendance, especially among the younger generation, is the main reason behind this. The National Museum is innovating through Ruang ImersifA, a 360˚ video mapping exhibition that utilizes the concept of metaverse tourism as a strategy to increase cultural appeal and educational value. This study uses a quantitative approach with primary data. The research population consists of tourists who visited the National Museum's Immersive Room. Data were collected through a Likert scale questionnaire and analyzed using the Spearman's rank correlation non-parametric statistical method. The results show that there is a positive and strong relationship between the independent and dependent variable, namely Attractiveness and Tourist Interest (r = 0,741, p = 0,000) and Digital Cultural Education and Tourist Interest (r = 0,675, p = 0,000) in the Immersive Space of the National Museum. The conclusion of this study is that digital-based technological innovations, such as those applied in the Immersive Space, are very effective as a dual strategy to create an attractive and educational experience, thereby increasing tourist interest in visiting the National Museum. It is recommended that managers continue to increase investment in digital infrastructure and enrich interactive educational content.Keywords: Tourist Attraction; Digital Cultural Education; Tourist Interest; Immersive Space; National Museum ABSTRAK Rendahnya minat kunjungan museum, terutama di kalangan generasi muda, menjadi latar belakang utama. Museum Nasional berimovasi melalui Ruang ImersifA, sebuah pameran video maping 360˚ yang memanfaatkan konsep metaverse tourism sebagai strategi untuk meningkatkan daya tarik dan nilai edukasi budaya. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis data primer. Populasi penelitian adalah wisatawan yang mengunjungi Ruang ImersifA Museum Nasional. Data dikumpulkan melalui kuisioner berskala likert dan dianalisis menggunakan metode statistik non-parametrik Uji Korelasi Rank Spearman. Hasil penelitian menunjukkan bahwa terdapat hubungan yang positif dan kuat antara variabel independen dan variabel dependen yaitu Daya Tarik dengan Minat Wisatawan (r = 0,741, p = 0,000) dan Edukasi Budaya Digital dengan Minat Wisatawan (r = 0,675, p = 0,000). Kesimpulan dari penelitian ini adalah inovasi teknologi berbasis digital, seperti yang diterapkan pada Ruang ImersifA, sangat efektf sebagai strategi ganda untuk menciptakan pengalaman yang menarik (attractive) sekaligus edukatif, sehingga mampu meningkatkan minat wisatawan untuk berkunjung ke Museum Nasional. Disarankan bagi pengelola untuk terus meningkatkan investasi pada infrastruktur digital dan memperkaya konten edukasi yang interaktifKata Kunci: Daya Tarik Wisata; Edukasi Budaya Digital; Minat Kunjungan Wisatawan; Ruang ImersifA; Museum Nasional